An Experimental Study of Acoustic Comfort in Open Space Banks Based on Speech Intelligibility and Noise Annoyance Measures - GOLMOHAMMADI, Rostam; Aliabadi, Mohsen; NEZAMI, Trifah (Archives of Acoustics, 2017)
Tasks requiring intensive concentration are more vulnerable to noise than routine tasks. Due to the high mental workload of bank employees, this study aimed to evaluate acoustic comfort in open-space banks based on speech intelligibility and noise annoyance metrics. Acoustic metrics including preferred noise criterion (PNC), speech transmission index (STI), and signal to noise ratio (SNR) were measured in seventeen banks (located in Hamadan, a western province of Iran). For subjective noise annoyance assessments, 100-point noise annoyance scales were completed by bank employees during activities. Based on STI (0.56 ± 0.09) and SNR (20.5±8.2 dB) values, it was found that speech intelligibilities in the workstations of banks were higher than the satisfactory level. However, PNC values in bank spaces were 48.2 ± 5.5 dB, which is higher than the recommended limit value for public spaces. In this regard, 95% of the employees are annoyed by background noise levels. The results show irrelevant speech is the main source of subjective noise annoyance among employees. Loss of concentration is the main consequence of background noise levels for employees. The results confirmed that acoustic properties of bank spaces provide enough speech intelligibility, while staff’s noise annoyance is not acceptable. It can be concluded that due to proximity of workstations in open-space banks, access to very short distraction distance is necessary. Therefore, increasing speech privacy can be prioritised to speech intelligibility. It is recommended that current desk screens are redesigned in order to reduce irrelevant speech between nearby workstations. Staff’s training about acoustic comfort can also manage irrelevant speech characteristics during work time.